Pengembangan Media Pembelajaran Berbasis Game Edukasi Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Materi IPAS Kelas V Sekolah - Wahyu Basri Lestari; Sugiyono Ardjaka; Ahmad Yani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research was motivated by the low critical thinking skills of fifth-grade students in the IPAS (Natural and Social Sciences) subject, a result of using conventional learning media that failed to capture student interest. The study aimed to produce valid, practical, and effective learning media to enhance students' critical thinking skills. It employed the Research and Development (R&D) method using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects were fifth-grade elementary school students in Cluster III, Gondang District. Two schools were selected as samples: SD Negeri 1 Wonokromo for the small-scale trial and SD Negeri 2 Tiudan for the large-scale trial. Data were collected using expert validation instruments, pre-tests and post-tests, and student response questionnaires. The results indicated that the developed educational game-based learning media met the